In situ normoxia enhances survival and proliferation rate of human adipose tissue-derived stromal cells without increasing the risk of tumourigenesis - Choi, J.R.; Pingguan-Murphy, Belinda; Wan Abas, Wan Abu Bakar; Yong, K.W.; Poon, C.T.; Noor Azmi, Mat Adenan; Omar, Siti Zawiah; Chua, K.H.; Xu, F.; Wan Kamarul Zaman, Wan Safwani (Public Library of Science, 2015)
Adipose tissue-derived stromal cells (ASCs) natively reside in a relatively low-oxygen tension (i.e., hypoxic) microenvironment in human body. Low oxygen tension (i.e., in situ normoxia), has been known to enhance the growth and survival rate of ASCs, which, however, may lead to the risk of tumourigenesis. Here, we investigated the tumourigenic potential of ASCs under their physiological condition to ensure their safe use in regenerative therapy. Human ASCs isolated from subcutaneous fat were cultured in atmospheric O-2 concentration (21 O-2) or in situ normoxia (2 O-2). We found that ASCs retained their surface markers, tri-lineage differentiation potential, and self-renewal properties under in situ normoxia without altering their morphology. In situ normoxia displayed a higher proliferation and viability of ASCs with less DNA damage as compared to atmospheric O-2 concentration. Moreover, low oxygen tension significantly up-regulated VEGF and bFGF mRNA expression and protein secretion while reducing the expression level of tumour suppressor genes p16, p21, p53, and pRb. However, there were no significant differences in ASCs telomere length and their relative telomerase activity when cultured at different oxygen concentrations. Collectively, even with high proliferation and survival rate, ASCs have a low tendency of developing tumour under in situ normoxia. These results suggest 2 O-2 as an ideal culture condition for expanding ASCs efficiently while maintaining their characteristics.